Individual Perceptions of the Criminal Justice System - Lochner, Lance (American Economic Review, 2003)
This paper empirically examines belief updating of the perceived probability of arrest and its criminal deterrence effects using two longitudinal data sources. While beliefs about the probability of arrest are positively correlated with local official arrest rates, they are unresponsive to information acquired from random individuals and local neighborhood conditions. Importantly, perceptions respond to changes in an individual's criminal and arrest history. Young males who engage in crime without getting arrested revise their perceived probability of arrest downward, while those who are arrested revise their probability upward. Estimates suggest that beliefs about the probability of arrest significantly deter crime. (JEL K42)